2021
DOI: 10.1177/2054358120987055
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis vs Peritoneal Dialysis: Comparison of Net Survival in Incident Patients on Chronic Dialysis in Colombia

Abstract: Background: In the area of nephrology, the practical application of relative survival methodologies can provide information regarding the impact of outcomes for patients with kidney failure on dialysis compared with what would be expected in the absence of this condition. Objective: Compare the net survival of hemodialysis (HD) and peritoneal dialysis (PD) patients in a cohort of incident patients on chronic dialysis in Colombia, according to the dialysis therapy modality. Design: Observational, analytic, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…concluded that the important difference between HD and PD was that the survival rate of patients on HD was higher than that of patients on PD, which was significant after 5 years of follow-up in 12,508 patients undergoing dialysis. 9 Similarly, Mukhopadhyay et al. concluded that the survival rate of patients on HD was higher than that of patients on PD after 5 years of follow-up in 130,324 patients undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…concluded that the important difference between HD and PD was that the survival rate of patients on HD was higher than that of patients on PD, which was significant after 5 years of follow-up in 12,508 patients undergoing dialysis. 9 Similarly, Mukhopadhyay et al. concluded that the survival rate of patients on HD was higher than that of patients on PD after 5 years of follow-up in 130,324 patients undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio realizado en Colombia con una cohorte de 12 508 pacientes mayores de 18 años, mostró una supervivencia similar a la encontrada en este estudio, con una tasa del 53 % a los cinco años de tratamiento 13 , otro estudio realizado en Indonesia, aunque con una cohorte más pequeña que incluía únicamente pacientes en diálisis peritoneal, encontró una supervivencia a los cinco años del 52 % 14 . Debido a la baja supervivencia en pacientes en diálisis, la detección de la ERC en etapas tempranas, y las acciones para retrasar la progresión de esta se consideran la mejor medida para alargar la vida de los pacientes renales 2 .…”
Section: Discussionunclassified
“…Los estudios que comparan las modalidades de tratamiento no sugieren hallazgos consistentes, mientras que en algunos se ha encontrado una mayor supervivencia en pa-cientes sometidos a hemodiálisis, como el estudio de cohorte colombiano mencionado anteriormente 13 ; en otras investigaciones no se ha encontrado diferencia significativa entre las modalidades de tratamiento 15,16 ; y, otros sugieren que las diferencias pueden estar relacionadas con una mayor carga de comorbilidades en un grupo u otro 15,17 . Por este motivo algunas guías clínicas recomiendan dejar la modalidad del tratamiento a elección del paciente, de acuerdo a sus necesidades y situación clínica 1,2 .…”
Section: Discussionunclassified
“…BRCS offers a person-centered approach with pre-dialysis education regarding dialysis modalities and shared decision-making between the patient, family, treating nephrologist, and clinical team. The relative balance between HD and PD, with 42.6% of the patients beginning on HD and 57.4% on PD [22], affords an excellent opportunity to compare survival outcomes between these 2 types of dialysis therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In the mid-2000s, our group published a study showing comparable survival between HD and PD in Colombia [23]. A more recent study reported higher relative survival for HD patients, although this analysis was a crude comparison [22]. The objective of this study was to compare the mortality of patients on the 2 dialysis modalities using propensity score matching (PSM) and to identify the variables associated with mortality.…”
Section: Introductionmentioning
confidence: 99%